Integrated chemical characterization, metabolite profiling, and pharmacokinetics analysis of Zhijun Tangshen Decoction by UPLC-Q/TOF-MS - Tong, Qingheng; Chang, Yueyue; Shang, Guanxiong; Yin, Jiu; Zhou, Xiaoqi; Wang, Suwei; Yan, Xiaofeng; Zhang, Fangfang; Wang, Suqin; Yao, Weifeng (Frontiers in Pharmacology, 2024)
Diabetes nephropathy (DN) has become the main cause of end-stage renal disease worldwide and has become a major public issue threatening the health of people all over the world. Therefore, it is essential to explore effective drugs for the treatment of DN. In this study, the Traditional Chinese Medicine (TCM) formula, Zhijun Tangshen Decoction (ZJTSD), a prescription modified from the classical formula Didang Decoction, has been used in the clinical treatment of DN. However, the chemical basis underlying the therapeutic effects of ZJTSD in treating DN remains unknown. In this study, compounds of ZJTSD, and serum after oral administration in rats were identified and analyzed by using UPLC-Q/TOF-MS. Meanwhile, the semi-quantitative approach was used to analyze the dynamic changes in compounds of ZJTSD in vivo. Based on UPLC-Q/TOF-MS analysis, 190 compounds from ZJTSD, including flavonoids, anthraquinones, terpenoids, phenylpropanoids, alkaloids, and other categories, were identified. A total of 156 xenobiotics and metabolites, including 51 prototype compounds and 105 metabolites, were identified from the compounds absorbed into the blood of ZJTSD. The results further showed that 23 substances with high relative content, long retention times, and favorable pharmacokinetic characteristics in vivo which deserved further investigations and validations of bioactivities. In conclusion, this study revealed the chemical basis underlying the complexity of ZJTSD, and investigated the metabolite profiling and pharmacokinetics of ZJTSD-related xenobiotics in rats, thus providing a foundation for further investigation into the pharmacodynamic substance basis and metabolic regulations of ZJTSD.